MODEL PELIBATAN MASYARAKAT DALAM PENGEMBANGAN EKOWISATA DI PUSAT INFORMASI MANGROVE - Nurhikmah Esti Prastika; Djauhar Edi Purnomo; Muhammad Fithrayudi Triatmaja (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah (Bappeda) Kota Pekalongan, 2016)
THIS STUDY AIMS TO IDENTIFY AND ANALYZE A MODEL OF ENGAGEMENT THAT CAN BE REALIZED BY THE COMMUNITY IN THE MANAGEMENT OF TOURISM BY THE PUBLIC AND OTHER INTERESTED PARTIES. THIS STUDY DESCRIBES A MODEL OF COMMUNITY INVOLVEMENT IN THE DEVELOPMENT OF ECOTOURISM IN MANGROVE INFORMATION CENTER PEKALONGAN CITY. THIS STUDY IS A QUALITATIVE RESEARCH. POPULATION IN THIS STUDY IS THAT PEOPLE WHO ARE AROUND THE OBJECT PEKALONGAN MANGROVE PARK IS THE ENTIRE LENGTH OF VILLAGE RESIDENTS NEW AND LONG CAGE. RSPONDEN NUMBER OF 100 RESPONDENTS CONSISTING OF A GROUP OF RESPONDENTS (STAKEHOLDER / OFFICIAL IN AN INSTITUTION AS MUCH AS 8 RESPONDENTS, EMPLOYERS AROUND PIM MUCH AS 2 RESPONDERS AND THE SURROUNDING COMMUNITY PIM MANY AS 90 RESPONDENTS). RESULTS FROM THIS STUDY IS THAT THE MODELS USED ARE MOSEL PELITABATAN COLLABORATIVE PARTNERSHIPS BETWEEN GOVERNMENT, COMMUNITIES AND EMPLOYERS AS WELL AS DEVELOPMENT OPPORTUNITIES THAT ENCOURAGE THE DEVELOPMENT OF PARTNERSHIPS IN THE MANAGEMENT OF MANGROVE PARK PEKALONGAN.